Controlled synthesis of aligned Ni-NiO core-shell nanowire arrays on glass substrates as a new supercapacitor electrode - Kim, Jin Young; Lee, Se-Hee; Yan, Yanfa; Oh, Jihun; Zhu, Kai (ROYAL SOC CHEMISTRY, 2012)
Aligned Ni-NiO core-shell nanowire arrays on a glass substrate were prepared via electrochemical deposition using porous alumina oxide templates. The core-shell nanowire electrodes displayed prominent supercapacitive behaviors. The rate capability of the electrodes depends strongly on the thickness of the NiO shell layers.
Keywords: CHARGE STORAGE MECHANISM; ELECTROCHEMICAL CAPACITORS; NICKEL-OXIDE; POROUS ALUMINA; FILMS; DENSITY; ROUTE